PENGARUH PENERAPAN METODE AUDIOLINGUAL TERHADAP KETERAMPILAN MENYIMAK BAHASA ARAB SANTRI PONDOK PESANTREN Al-ITTIFAQIAH - Elza_ Apriliyah Anggraini (Program Studi Pendidikan Bahasa Arab Fakultas Tarbiyah IAI Al-Qur'an Al-Ittifaqiah Indralaya, 2025)
Listening skills are an essential component in the process of learning Arabic, serving as a foundation for the development of other language abilities. One method considered effective in improving listening skills is the Audiolingual method, which focuses on repetitive practice, imitation, and the development of language habits through speech patterns. This study aims to measure the impact of implementing the Audiolingual method on Arabic listening comprehension. The research employed a quasi-experimental method with a pretest???posttest control group design. The sample consisted of students divided into two groups: the experimental group, which received treatment using the Audiolingual method, and the control group, which learned through traditional methods. Data were collected using listening comprehension tests administered before and after the treatment. The data were analyzed using statistical tests to determine whether there was a significant difference between the two groups. The results showed that the implementation of the Audiolingual method had a significant effect on improving Arabic listening skills. Students in the experimental class demonstrated better score improvement compared to those in the control class.